2023
DOI: 10.3390/microorganisms11061538
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Dependent and Metabarcoding Characterization of the Sugar Beet (Beta vulgaris L.) Microbiome for High-Yield Isolation of Bacteria with Plant Growth-Promoting Traits

Tamara Krstić Tomić,
Iva Atanasković,
Ivan Nikolić
et al.

Abstract: The diversity of plant-associated bacteria is vast and can be determined by 16S rRNA gene metabarcoding. Fewer of them have plant-beneficial properties. To harness their benefits for plants, we must isolate them. This study aimed to check whether 16S rRNA gene metabarcoding has predictive power in identifying the majority of known bacteria with plant-beneficial traits that can be isolated from the sugar beet (Beta vulgaris L.) microbiome. Rhizosphere and phyllosphere samples collected during one season at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In our study, a metabarcoding approach was used to characterize bacterial diversity in seeds of sugar beet hybrids. Notably, this study represents the pioneering investigation into the bacterial diversity of these hybrids using two distinct methodologies, with the exception of the rhizosphere of the Eduarda hybrid, which has been previously explored [ 51 ]. Bacterial community richness and alpha diversity analysis showed that the microbial communities of sugar beet hybrids were more diverse in ED, KO, and T seeds than in C and TF hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a metabarcoding approach was used to characterize bacterial diversity in seeds of sugar beet hybrids. Notably, this study represents the pioneering investigation into the bacterial diversity of these hybrids using two distinct methodologies, with the exception of the rhizosphere of the Eduarda hybrid, which has been previously explored [ 51 ]. Bacterial community richness and alpha diversity analysis showed that the microbial communities of sugar beet hybrids were more diverse in ED, KO, and T seeds than in C and TF hybrids.…”
Section: Discussionmentioning
confidence: 99%